Potencialidade e desafios dos contratos inteligentes no Brasil: uma perspectiva da inovação no setor jurídico - Sanas, Caio Fernando [UNIFESP] (2021)
Innovation affects all sectors of the economy including the legal sector. The number of technologybased emerging companies in the legal sector has been increasing each year with various technological solutions in the public and private sectors. Among the theories on best innovation management practices, the search for signs and information in the market that there is potential innovation is a preponderant factor to identify possible innovative activity in the sector. After searching for information, it will be up to the manager to select which ones to react to and how to react, so that eventually a certain product or service will be implemented, and the value will be captured. Currently, the legal sector has focused on studies about smart contracts based on blockchain technology. In this sense, applying the theory of innovation management to investigate this phenomenon is essential to identify the potential and challenges of technology in Brazil, especially by the legal sector, whether by the public sector or by the private sector. The purpose of this research is to investigate the potentials and challenges of smart contracts based on blockchain technology by legal professionals. Methodologically, it was decided to collect information about smart contracts based on blockchain technology through exploratory research; techniques of the systematic literature review were used to identify the main channels of publication on the topic. Subsequently, a phenomenological qualitative approach was carried out with field research, collecting empirical data, through interviews with market professionals specialized in the subject. Data was collected through interviews conducted by Zoom and Microsoft Teams and analyzed using the content analysis method, with the aid of the Atlas TI Cloud software. It is concluded that smart contracts based on blockchain technology, have high potential in the legal sector, and can be considered as an innovation in the way legal professionals can provide their services, per hour, in a specific niche such as cryptoeconomics. Concerning the challenges, it was found essentially the need for interdisciplinarity in the studies of all professionals who interact in this market, such as economists, developers, and lawyers; dissemination of knowledge in the academic and professional fields; and the adoption of crypto assets by the market. It is therefore evident that there is a need for interdisciplinary dialogue to create legal solutions using smart contracts; this is what the present study proposes. In addition to the results, the research contributes to highlighting the main aspects of smart contracts in Brazil with a focus on the legal sector, without losing, however, the interdisciplinarity that the theme requires, serving as a basis for studies for those who intend to understand technology, at the point theoretical and practical point of view. From the point of view of the traditional innovation management literature, the present research started in the search for information, and through the methodology used, it selected the main information, so that it serves as a basis for the implementation of solutions and value capture, of new services and products.